Features of Preparation of Creative Professionals in the Educational Environment of the Modern University - Eliseeva, Elena; Makarova, Galina; Feshchenko, Valentina; Komarova, Svetlana; Kazimirova, Natalia; Sevryukova, Svetlana (International Review of Management and Marketing, 2016)
This paper presents a systematic approach to the problem of forming creative professionals in the context of university education. The essence of creative and innovative economy of the information society, the hierarchical structure of its intellectual potential. The representation of the creative class and its role in the development of modern society, about the possibilities of this new class due to its particular set of qualities, properties and characteristics. The role of modern educational institutions in the training of creative professionals, the necessity of the implementation of a number of areas of restructuring the education system to ensure the transition from education to the advanced ascertaining and perspective, reproductive education for creativity. Special attention is paid to the environmental factor and its role in shaping today demanded professional creative person. Characterize the structure of the information-educational environment and its components. The concept of the model and creative educational environment, the ways and means of transforming the current educational environment in the creative environment of formation of creative professionals. Keywords: informational and educational environment, creative professional, creative class JEL Classifications: G32; O30